Impact of diabetes in the Friedreich ataxia clinical outcome measures study. Issue 9 (26th July 2017) - McCormick, Ashley; Farmer, Jennifer; Perlman, Susan; Delatycki, Martin; Wilmot, George; Matthews, Katherine; Yoon, Grace; Hoyle, Chad; Subramony, Sub H.; Zesiewicz, Theresa; Lynch, David R.; McCormack, Shana E.
Abstract: Objective: Friedreich ataxia (FA) is a progressive neuromuscular disorder caused by GAA triplet repeat expansions or point mutations in the FXN gene. FA is associated with increased risk of diabetes mellitus (DM). This study assessed the age‐specific prevalence of FA‐associated DM and its impact on neurologic outcomes. Research Design and Methods: Participants were 811 individuals with FA from 12 international sites in a prospective natural history study (FA Clinical Outcome Measures Study, FACOMS). Physical function was assessed, using validated instruments. Multivariable regression analyses examined the independent association of DM with outcomes. Results: Mean age of participants was 30.1 years (SD 15.3, range: 7–82), 50% were female, and 94% were non‐Hispanic white. 9% (42/459) of adults and 3% (10/352) of children had DM. Individuals with FA‐associated DM were older ( P < 0.001), had longer GAA repeat length on the least affected FXN allele ( P = 0.037), and more severe FA ( P = 0.0001). Of individuals with DM, 65% (34/52) were taking insulin. Even after accounting statistically for both age and GAA repeat length, DM was independently associated with greater FA symptom burden ( P = 0.010), reduced capacity to perform activities of daily living ( P = 0.021), and a decrease of 0.33 SDs on a composite performance measure (95% CI: −0.56–0.11, P = 0.004); the relative impact of DM was most apparent in younger individuals. Conclusions: DM‐associated FA has an independent adverse impact on well‐being in affected individuals, particularly at younger ages. In future, evidence‐based approaches for identification and management of FA‐related DM may improve both health and function.